Estudo químico e biológico do fungo basidiomiceto Neonothopanus gardneri (Berk. Ex Gardner) e avaliação de plantas com atividade de luciferina fúngica - Santos, Patricia Dias [UNIFESP] (2017)
Basidiomycetes have been widely used in biotechnological processes, mainly due to the production of bioactive polysaccharides. Neonothopanus gardneri (Berk. ex Gardner) is a basidiomycete that can emit light, popularly known as “flor-de-coco”, is found exclusi- vely in South America. The substance responsible for bioluminescence in basidiomycete is 3-hydroxy-hispidin, biosynthesized by hydroxylation of the precursor molecule hispidin, ca- talyzed by hispidin-3-hydroxylase -NAD(P)H-dependent-, resulting in the release of energy in the form of visible and cold light. This substance presents low stability and is accumulated in the basidiomycete in small proportions, once it is consumed during the bioluminescent reaction. To date, no substance with light emission activity from plants has been reported in the literature. Styrylpyrone-class derivatives with a similar structure to hispidin or fungal luci- ferin can be found in several plants, such as Piperaceae, Zingeberaceae and Equisetaceae, and are biosynthesized from reactions catalyzed by styrylpyrone synthase. In this context, it appears as hypothesis of the present work if plants are able to biosynthesize organic com- pounds with light emission activity when hydroxylase and/or luciferase enzymes are exposed in the presence or absence of NAD(P)H. Thus the objective of this study was to evaluate the chemical profile of N. gardneri and the activity of fungal luciferin in ancient, intermediate and recent plant species according to phylogenetic classification. From the 41 species of plants evaluated for fungal luciferin activity, 10 showed light emission in the absence of NAD(P)H, and the species Cattleya sp., Phalaenopsis sp., Casearia sylvestris and Piper tuberculatum showed higher intensity of Light compared to the other species evaluated and compared with the control (3-hydroxy-hispidin). It can be concluded that some vascular plants have luciferin with fungal 3-hydroxy-hispidin activity and react directly with luciferase without the need for addition of NAD(P)H and therefore are capable of emitting light. In addition, the aqueous ex- tract was obtained from N. gardneri mycelia using the solvent accelerated extraction (ASE) technique. From the aqueous extract the polysaccharide fraction was obtained by precipita- tion with ethanol, followed by freezing and thawing processes, Fehling solution precipitation, and dialysis by membranes of different porosities. From these purification steps three dif- ferent polysaccharides were obtained which were then characterized by GC-MS and uni and bidimensional NMR spectroscopy. The main monosaccharide observed was glucose in percentages above 90% in two of them. The glycosidic linkage type wasd 1→6 with β and configurations observed in one of them. The crude extract as well as the fractions obtained during the several steps were also evaluated for cytotoxic activity against four tumor cell li- nes, and no significant activity was observed, suggesting that these polysaccharides may present antitumor activity through other mechanisms.